Tuos and the foregrounding of gahum in the sugidanon epics tikum kadlum and amburukay. - Rebong, Adhoniz B.
This study examines the concepts of gahum and tuos in the Sugidanon epics of Panay entitled Tikum Kadlum and Amburukay. It examines the text by identifying the factors which manifest gahum and tuaos, analyze their usage, and reveal the relevance of both concepts to the babaylanic worldview in the epic narrative. The analysis explains that (1) honor, notoriety, authority, wealth, supernatural capacity, and warrior prowess contribute to the manifestation of gahum, (2) the manifestation and usage of gahum vary depending on the influence of kinship ties and customary traditions, (3) gahum follows a specific patter of conflict, imposition, retaliation, and resolution, as seen in the interactions outside familial relationships, (4) tuos grants gahum to and individual through the absolute gahum of the communal laws, and (5) gahum and the gahum sang tuos originates from the power of the indigenous worldview over the lives of the characters in the Sugidanon epics.